Evaluation of ice particle growth in ICON using statistics of multi‐frequency Doppler cloud radar observations. (7th September 2020) - Ori, Davide; Schemann, Vera; Karrer, Markus; Dias Neto, José; von Terzi, Leonie; Seifert, Axel; Kneifel, Stefan
Abstract: Vertically pointing radar observations combining multiple frequencies and Doppler measurements have been recently shown to contain valuable information about ice particle growth processes, such as aggregation and riming. In this study, we use a two‐months X, Ka, W‐Band Doppler radar dataset of midlatitude winter clouds to infer statistical growth signatures of ice and snow particles. The observational statistics are compared to forward‐simulated radar moments based on simulations of the campaign time period with a high‐resolution version of the ICON model and a two‐moment microphysical scheme. The statistical comparison shows very good agreement of the simulated vertical structure of radar reflectivity and surface precipitation rate. The dual‐wavelength ratios, which are closely related to the mean particle size, also show consistently a major increase at temperatures higher than –15 °C. However, at temperatures higher than –7 °C, ICON increasingly overestimates the mean particle size. The statistics of mean Doppler velocities also reveal that the model overestimates the terminal velocity of snow particles, especially at larger sizes. We discuss possible reasons for the identified discrepancies, such as an unrealistic temperature dependence of the sticking efficiency or the non‐saturation of terminal velocities at larger sizes caused by the implemented power law relations. Our study demonstrates examples of the importance of combining various radar techniques for identifying issues in simulated microphysical processes, which can otherwise be hidden due to compensating errors. Abstract : Numerical weather prediction model output is compared with multi‐frequency Doppler radar observations. The statistical comparison reveals discrepancies in the cloud structure that suggest the presence of some inaccuracies in the modelled ice properties. The study demonstrates the importance of combining various radar techniques (such as multi‐frequency and Doppler) for revealing these discrepancies which otherwise might remain hidden by the effect of compensating errors.